The Influence of Servant Leadership and Its Impact on Organizational Citizenship Behavior (OCB) Lecturers at the Lombok Business Academy - Muhammad Azim; Moh. Salman Alfarisi; I Putu Buda Yasa; Aprilla Sinta Uli; Ni Kadek Wahyuni Merta Sari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the influence of servant leadership on the Organizational Citizenship Behavior (OCB) of lecturers at the Lombok Business Academy. Servant leadership is considered an important leadership style in higher education because it emphasizes service, empathy, empowerment, support, and the development of subordinates. Meanwhile, OCB refers to voluntary behavior beyond formal duties that contributes to organizational effectiveness. This research employed a quantitative approach with a causal associative design. The population consisted of all active lecturers at the Lombok Business Academy, and the sampling technique used was saturated sampling. Data were collected through questionnaires using a Likert scale, supported by observation and documentation. The data were analyzed using SPSS through validity testing, reliability testing, classical assumption testing, simple linear regression analysis, t-test, and coefficient of determination. The results indicate that servant leadership has a positive and significant effect on lecturers’ Organizational Citizenship Behavior. The regression coefficient shows that an increase in servant leadership is followed by an increase in lecturers’ OCB. Therefore, the implementation of servant leadership should be continuously strengthened to create a supportive, harmonious, and productive academic work environment at the Lombok Business Academy.